The Pervasive role of campaign and product-related uncertainties in inhibiting crowdfunding success - Christian Hopp; Stefan Rose; Jermain Kaminski (Journal of Risk and Financial Management, 2022)
In this research, we study the funding decision in crowdfunding from the perspective of potential backers. We assess whether perceived uncertainty affects the decision to contribute to crowdfunding campaigns. For this purpose, we conduct a 2 2 between-subjects experiment with different stages of product development and the perceived innovativeness of products depicted in campaigns. Our findings show that an early development stage positively affects perceived uncertainty, adversely affecting the willingness to contribute. Simultaneously, higher perceived innovativeness elicits higher uncertainty perceptions, negatively influencing the willingness to contribute. Our research furthers an understanding of entrepreneur perspective taking to overcome uncertainty perceptions from the indeterminacy of crowdfunding campaigns.
Keywords: 650; crowdfunding; entrepreneurial financing; experimentation; new product development; psychology of innovation; uncertainty